Optimal Monthly Room Allotment by Season: Case Study for Hotel in Chonburi - Saijumpa, Apiwat; Amaruchkul, Kannapha (Journal of Applied Statistics and Information Technology, 2018)
In this study, we want to determine an optimal allocation for hotel rooms in order to maximize the total expected profit. Specifically, we want to determine the allocation for each group of customers, whose demands and selling prices are different. After finding the suitable allocation by month and by season for each group, we also determine the minimum revenue such that we would accept the booking request. The proposed policy was compared to the current policy in January – March 2018: We found that the revenue of the hotel would have been increased by 1,248,198 THB for room allotment by month and revenue increased by 1,187,451 THB for room allotment by season, if our policy had been implanted. The minimum booking price for travel agent group from Monday to Friday were 1,600 THB/night, and Saturday to Sunday were 1,650 THB/night.